Core training: Stabilizing the confusion - Faries, M. D.; Greenwood, M. (Strength and Conditioning Journal, 2007)
Confusion exists regarding what the core musculature is, how it is evaluated, how it is trained, and how it is applied to functional performance. The core musculature is divided into 2 systems, local (stabilization) and global (movement), with distinction between core-strength, core-stability, and functional exercises.